Sudan : Humanitarian Crisis, Peace Talks, Terrorism, and U.S. Policy. (U.S. Congressional Research., 2001)
Provides background on humanitarian crisis in Sudan brought on by civil war and drought, and addresses recent developments and prospects for negotiation. Examines U.S. and international responses to the humanitarian situation in Sudan, Sudanese support of terrorism, Sudan and oil development, religious persecution and slavery in Sudan, and current U.S. policy debate.